The Effects of Responsible Gambling Pop-Up Messages on Gambling Behaviors and Cognitions: A Systematic Review and Meta-Analysis - Bjørseth, Benjamin; Simensen, Josefine Oudmayer; Bjørnethun, Aina; Griffiths, Mark D.; Erevik, Eilin K.; Leino, Tony; Pallesen, Ståle (Frontiers in Psychiatry, 2021)
Pop-up messages are normally presented to gamblers during gambling in order to prevent excessive gambling and to adjust gambling-promotive cognitions. The effect of such messages on gambling behavior and gambling cognitions has however previously not been synthesized quantitatively. Consequently, a meta-analysis estimating the effects of pop-ups on gambling behavior and cognitions was conducted. A systematic literature search with no time constraints was performed on Web of Science, PsychInfo, Medline, PsychNET, and the Cochrane Library. Search terms included “gambling”, “pop-up”, “reminder”, “warning message” and “dynamic message”. Studies based on randomized controlled trials, quasi-experimental designs and pre-post studies reporting both pre- and post-pop-up data were included. Two authors independently extracted data using pre-defined fields including quality assessment. A total of 18 studies were included and data were synthesized using a random effects model estimating Hedges g. The effects of pop-ups were g=0.413 (95%CI=0.115-0.707) and g=0.505 (95%CI=0.256-0.746), for cognitive and behavioral measures, respectively. For both outcomes there was significant between-study heterogeneity which could not be explained by setting (laboratory vs. naturalistic) or sample (gambler vs. non-gamblers). It is concluded that pop-up messages provide moderate effects on gambling behavior and cognitions short-term and that such messages, given their limited costs and resources, play an important role in the arsenal of responsible gambling tools.